2016
DOI: 10.1590/s1519-99402016000200006
|View full text |Cite
|
Sign up to set email alerts
|

Increasing levels of concentrate digestibility, performance and ingestive behavior in lambs

Abstract: SUMMARY The objectives of this research were to determine the effects increasing levels of concentrate on nutrients digestibility, performance, economic viability of diets and ingestive behavior of lambs. Fifteen crossbred lambs were used in a randomized complete block design according to initial body weight and age. Lambs were penned individually during 55 days, being 10 days for adaptation of diets and 45 days for data collection. The treatments consisted in three isonitrogenous diets with increasing levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 16 publications
0
6
0
9
Order By: Relevance
“…The supply of higher proportions of concentrate has been proposed as a way to increase digestibility and consequently increase weight gain and carcass yield. Parente et al (2016) observed that DM digestibility increased linearly with increasing levels of concentrate in lamb diets.…”
Section: Discussionmentioning
confidence: 93%
“…The supply of higher proportions of concentrate has been proposed as a way to increase digestibility and consequently increase weight gain and carcass yield. Parente et al (2016) observed that DM digestibility increased linearly with increasing levels of concentrate in lamb diets.…”
Section: Discussionmentioning
confidence: 93%
“…A linear increase for feeding time and rumination was observed with bagasse increasing levels, and a linear decrease of idle time (Table 4). The animals spent more time ingesting feed; nevertheless, they presented lower DM intake ( Table 3), suggesting that greater NDF in diets with more inclusion of bagasse increased animal selectivity (Parente et al, 2016) and, as a consequence, feeding efficiency was lower. The highest values observed for rumination time can be justified by the highest NDF intake observed for diets with greater bagasse inclusion.…”
Section: Resultsmentioning
confidence: 99%
“…O uso de dieta de alto grão para animais ruminantes de pequenos portes tem mostrado ser mais eficiente do que para bovinos. Os ovinos são mais eficientes na mastigação e seleção dos grãos inteiros, melhorando assim seu aproveitamento (PARENTE et al, 2016). O uso de probiótico em dieta de alto grão é pouco usado, contudo estudos têm demonstrado que a adição de probiótico à dieta tem contribuído para o aumento de desempenho animal (RIGOBELO; CARDOZO; MACHADO, 2014).…”
Section: Ovinocultura De Corteunclassified
“…Em trabalhos mais recentes sobre dietas com grão inteiro, principalmente milho, sorgo e milheto, a relação grão/núcleo (mineral, vitamínico e proteico), é de 85:15%, respectivamente (DIAS et al, 2016;FRUET et al, 2016;PARENTE et al, 2016), sendo o núcleo um complemento àa deficiência do grão para atender às exigências dos ruminantes. São observadas também outras relações, tais como, 60:40% -concentrado:núcleo (GRILLI et al, 2016;ABAKER et al, 2017;ZHANG et al, 2018) ou 65:20:15% -grão:volumoso:núcleo, sendo que nessa última condição o volumoso tem como objetivo aumentar a fonte de fibra na dieta (OLIVEIRA et al, 2015a;FRUET et al, 2016).…”
Section: Dietas Com Alta Concentração De Grão Energéticounclassified
See 1 more Smart Citation